Recent Advances in Understanding Hormonal Therapy Resistant Prostate Cancer - Donkena, K.V.; Yuan, H.; Young, C.Y. (Current Cancer Drug Targets, 2010)
Androgen deprivation therapy has been the major treatment for advanced prostate cancer (PCa) and has shown to prolong life. However, remissions are temporary and patients almost inevitably progress to become castration-resistant prostate cancer (CRPC). CRPC is almost incurable even when treated with docetaxel that may have a slight life prolonging effect on CRPC patients. Interestingly, most of CRPC still express androgen receptor (AR) and depend on the AR for growth. Recently it has been suggested that AR may act as a tumor suppressor in normal prostatic epithelial cells, while in PCa cells AR becomes oncogenic, even under androgen deprivation states. The mechanisms for the latter are still under intensive investigations. A number of studies showed that, in fact, AR signaling is increased under an androgen-depleted environment. The mechanisms suggested in these studies including AR mutations, AR overexpression by gene amplification and other mechanisms that allow activation by low androgen levels or by other endogenous steroids, increased local de novo synthesis of androgens will be discussed. Moreover, developments and tests in clinical trials in CRPC of a number of novel agents interrupting AR signaling mediated PCa growth will also be discussed.
Keywords: Androgen receptor